Boilable cassava varieties: what is their role within the context of the global agricultural economy? - Ngeve, J.M.; Tenku, S.N.; Dixon, Alfred G.O.; Whyte, J.B.A.; Okechukwu, R.U.; Hanna, R.; Akoroda, M.O. (2010)
Cassava production and utilization in Cameroon have undergone a long evolution. The post-independenceand pre-1990 eras were marked by activities that considered cassava to be a subsistence food crop. Duringthis period, farmers relied on coffee and cocoa as the major cash crops. Cassava growers used mainly boil–and–eat varieties that could be sold in local markets.. The crop gradually became important as a cash cropwhen coffee and cocoa prices fell in the world market. In recent years, cassava has gained prominence in allparts of the country where the crop is now grown for cash. Varieties responding to this market demand havehad to be developed and disseminated to growers. The issue of the types of varieties needed to give cassavaits place in the world market needs to be revisited. Effective processing and high quality control of processedproducts have to be addressed adequately for cassava to insert itself in the global economy